Chemical Control of Mango Anthracnose in Malaysia. In vitro Fungitoxicity of Selected Chemicals - Lim, T. K. (1980)
Fifteen fungicides and two commercial formulations of the insecticicie, dicrotophos, were investigated for in vitro fungitoxicity against mango anthracnose pathogen, Colletotrichum gloeosporioides. Among the fungicides tested, the pathogen was extremely sensitive to the thiophanate, the bellzimidazoles and two of the N-trichloromethylthio group of fungitoxicants which exhibited ED so of less than 5 pg/ml. The dithiocarbamates varied in their degree of toxicity, with ED so ranging from 100 pg/ml to 580 pg/ml. The two miscellaneous fungicides, chlorothalonil and iprodione alld the two insecticides showed extremely low and negligible fungitoxicity, repectively. Similarities and differences between and within groups of fungicides tested are further discussed in relation to their chemical structures, biochemical modes of actions and formulations.